Diversity of human parechovirus in infants and children with acute gastroenteritis in Japan during 2014–2016 - Ngan Thi Kim Pham (2019)
© 2019 Elsevier B.V. A total of 972 stool samples were collected from infants and children with acute gastroenteritis (AGE) in pediatric clinics encompassing six localities (Hokkaido, Tokyo, Shizuoka, Kyoto, Osaka, and Saga) in Japan during the 2-year period from July 2014 to June 2016. Sixty six of the samples (6.8%) were found to be positive for human parechovirus (HPeV) by multiplex reverse transcriptase-polymerase chain reaction (RT-PCR) and subjected to genotyping based on viral protein 1 (VP1) sequences. Four different HPeV genotypes consisting of HPeV1, -3, -4 and -6 were detected, with HPeV1 clade B being predominant and followed by HPeV3 and -6. The first-time presence of HPeV1 clade A in Japan and rare HPeV4 were noted. This study provides up-to-date information on the genetic diversity of HPeV circulating in Japanese infants and children with AGE.